Piper hongheense (Piperaceae), a new species from Yunnan, China - Fan, Rui; Zhao, Wen-Jing; Su, Fan; Li, Yang; Ji, Xun-Zhi; Su, Bao-Fen; Xia, Nian-He; Hao, Chao-Yun (Phytotaxa, 2025)
Piper hongheense (Piperaceae), a new species from Yunnan Province of China, is here described and illustrated. Morphologically it is similar to Piper boehmeriifolium and Piper boehmeriifolium var. glabricaule, from which it can be easily distinguished by the combination of characters: height 0.7–1 m, leaves oblong-lanceolate to lanceolate, 10–16 cm × 2.5–4 cm, infructescences ±0.6 cm in diam., berries and bracts white when mature. The description of the new species includes photographs, a detailed description, notes on etymology, distribution and habitat, as well as a comparison with morphologically similar species.